2014
DOI: 10.1186/1471-2482-14-88
|View full text |Cite
|
Sign up to set email alerts
|

Banded gastric bypass - four years follow up in a prospective multicenter analysis

Abstract: BackgroundThe gastric bypass is the gold standard of bariatric surgery. Nevertheless some patients show insufficient weight loss or weight regain. Dilation of the pouch or the pouch outlet may be the cause. The banded gastric bypass tries to overcome dilation by placing an implant around the pouch or pouch outlet. In this study we describe our results using the GaBP™ ring system in banded gastric bypass operations in 3 bariatric centers.Methods183 patients in 3 bariatric reference centers received a banded gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
1
6
0
2
Order By: Relevance
“…Resolution of hypertension, SA and dyslipidaemia was comparable in both groups. These outcomes are consistent with what has been reported in the literature …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Resolution of hypertension, SA and dyslipidaemia was comparable in both groups. These outcomes are consistent with what has been reported in the literature …”
Section: Discussionsupporting
confidence: 93%
“…These outcomes are consistent with what has been reported in the literature. 12,17 The incidence of nutrient, haemoglobin, albumin and protein deficiencies were higher at all times of follow up in this study in the OAGB group compared to the BGBP group (Table 4). Both operations are prone to iron and B12 deficiencies because of bypass of the duodeno-jejunal axis.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Many factors are probably responsible for the poor outcome after SG, including initial BMI, changes in dietary habits, and sleeve dilation (28)(29)(30). For these reasons, some authors have described implantation of a band or ring around the proximal sleeve pouch to improve weight loss and maintenance as in the BRYGB procedure (31)(32)(33)(34)(35). In our study, the BSG group showed a significant difference compared with the rest reported %EBWL of 66.74% and %TBWL of 38.2% after BSG, which were significantly greater than those in the SG patients in their study.…”
Section: Discussionmentioning
confidence: 99%